PEMBUKTIAN TERBALIK: SUATU KAJIAN TEORETIS TERHADAP TINDAK PIDANA KORUPSI - Samosir, Agustinus (Fakultas Hukum Universitas Bangka Belitung, 2017)
The existence of reversing the burden of proof from the perspective of legislation policy is known in the criminal act of corruption as a